2010
DOI: 10.1051/forest/2010033
|View full text |Cite
|
Sign up to set email alerts
|

Modelling coarse woody debris in Pinus spp. plantations. A case study in Northern Spain

Abstract: Abstract• Coarse woody debris (CWD) plays a substantial role in several ecological processes in forest ecosystems, providing a habitat for many organisms and participating in biogeochemical fluxes. Understanding CWD dynamics is important to classify adequate density, size and amount into different decay classes and to make decisions that include biodiversity and the carbon budget in practical forestry.• A two-step model has been developed to quantify CWD in Pinus spp. plantations in Northern Spain. The two-ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
(37 reference statements)
0
9
0
1
Order By: Relevance
“…Even-age silvicultural management is typically used on public lands in this region and consists of clearcutting followed by natural regeneration, pre-commercial thinning and a low thinning regime when economically feasible. Previous research has indicated that thinning increased CWD abundance in this area (Herrero et al 2010 , 28.84 Mg ha -1 in ponderosa and lodgepole pine forests in the NW USA. Despite differences in species, ecological conditions and management histories, in all four ecosystems the mean snag volume was less than that of logs, most of the CWD mass was in an intermediate degree of decay, and mature stands had the greatest amount of CWD mass, followed by middle-age and then young stands.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Even-age silvicultural management is typically used on public lands in this region and consists of clearcutting followed by natural regeneration, pre-commercial thinning and a low thinning regime when economically feasible. Previous research has indicated that thinning increased CWD abundance in this area (Herrero et al 2010 , 28.84 Mg ha -1 in ponderosa and lodgepole pine forests in the NW USA. Despite differences in species, ecological conditions and management histories, in all four ecosystems the mean snag volume was less than that of logs, most of the CWD mass was in an intermediate degree of decay, and mature stands had the greatest amount of CWD mass, followed by middle-age and then young stands.…”
Section: Introductionmentioning
confidence: 74%
“…Even-age silvicultural management is typically used on public lands in this region and consists of clearcutting followed by natural regeneration, pre-commercial thinning and a low thinning regime when economically feasible. Previous research has indicated that thinning increased CWD abundance in this area (Herrero et al 2010). Forestry in NW Russia is characterized by an established, relatively long rotation system with © SISEF http://www.sisef.it/iforest/ 53 iForest (2014) 7: 53-60…”
Section: Introductionmentioning
confidence: 99%
“…Tree mortality contributes to coarse woody debris (CWD), a key carbon reservoir in mature and old-growth forests. Differences in CWD stocks have been found among forest types (Herrero et al, 2010 and2014a). The decomposition rates of dead woody materials varies with the species, size, type of material (i.e., bark, sapwood or heartwood), and site conditions (i.e., temperature, humidity, etc.).…”
Section: Rotation Lengthmentioning
confidence: 99%
“…Deadwood is recognized as an essential component in forest stands, particularly with regard to biodiversity conservation and ecosystem functioning, and it represents an important forest carbon pool (Rondeux et al, 2012). Forest inventories provide data to estimate this carbon pool (e.g., Harmon & Marks, 2002) and although deadwood estimates for Mediterranean forests are scarce, the importance of deadwood in carbon storage and the influence of forest management have gained prominence in recent years (e.g., Lombardi et al, 2008;Herrero et al, 2010;Paletto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%